Fertility, Female Labor Supply, and Family Policy - Daniela Ujhelyiova; Hans Fehr (Verein für Socialpolitik, 2010)
The present paper develops a general equilibrium model with overlapping generations and endogenous fertility in order to analyze the interaction between public policy and household labor supply and fertility decisions. The models benchmark equilibrium reflects the current family policy as well as the differential fertility pattern of educational groups in Germany. Then we simulate alternative reforms of child benefits and family taxation which increase the fertility rate and the long-run growth rate of the economy. Our simulations indicate two general results: First, due to higher taxation households are typically hurt by the first-order effects of family policy but benefit from the effects of the repercussion effects from the change in the population structure. Second, it is possible to generate a joint increase of the fertility rate and female employment rate as observed in cross-country studies. Third, it is possible to increase fertility without hurting any skill class living in the long run.
Keywords: J13; J22; C68; 330; stochastic fertility; general equilibrium life cycle model